Mechanical behavior and essential work of fracture of surface‐modified exfoliated graphite filled polypropylene/ethylene‐vinyl acetate blend nano‐composites. Issue 20 (4th March 2023) - Fotoohi, Abuzar; Ashenai Ghasemi, Faramarz; Fasihi, Mohammad; Rajaee, Pouya
Abstract: Polymer nano‐composites have an extensive diversity of applications in many areas, including automotive, construction, healthcare, and electronics. Excellent tensile and fracture properties are commonly required to achieve the appropriate properties. In this research, the tensile and fracture behavior of polypropylene (PP)/ethylene‐vinyl acetate (EVA)/exfoliated graphite (EG) blend nano‐composites are investigated. The exfoliated graphite was either unmodified or surface‐modified with ammonium polyphosphate (APP). When the modified exfoliated graphite (EG‐g‐APP) was added to PP/EVA compounds, the tensile properties were more enhanced compared to unmodified EG. The elongation at break was around 2 times greater in the blend containing EG‐g‐APP. The essential work of fracture (EWF) approach was utilized to evaluate the effect of EG and EG‐g‐APP on the fracture behavior of PP/EVA blends. The w e and βw p values of the nano‐composites including EG‐g‐APP were mainly higher than nano‐composites containing EG at the same nano‐filler concentration. Also, according to SEM imaging, the EWF analysis results suggested that the preeminent mechanism of fracture in various compounds is the debonding of EVA from PP, which causes shear yielding and fibrillar structures on the surface of the compounds. It was observed that as EVA increased, the number of cavities and the size of fibrillar structures were increased. Enhancement in fracture toughness and matrix resistance was attributed to a growth in the number of nano‐voids and a decrease in voids' size. Abstract : Schematic representation of the materials, characterizations and experiments in this study.